Optical coherence tomography angiography as an indicator of the efficacy of treatment for choroidal neovascularization - F. A. Bakhritdinova; Z. R. Maksudova; N. A. Usmanova; F. M. Urmanova (Ukrainian Society of Ophthalmologists, 2022)
Background: Choroidal neovascularization (CNV) occurs in as much as 11.3% of patients with pathological myopia, and is a major cause of visual disability associated with irreversible loss of central vision. The advent of optical coherence tomography angiography (OCTA) has opened up new opportunities for objective documentation and real-time qualitative and quantitative evaluation of CNV in the course of therapy. Purpose: To assess the efficacy of anti-vascular epithelium growth factor (VEGF) therapy with ranibizumab in CNV associated with pathological myopia using OCTA. Material and Methods: Thirty seven anti-VEGF-treatment naive patients (37 eyes) with myopic CNV were involved in the study. All study participants received an intravitreal ranibizumab injection (in accordance with the manufacturer's recommendations) followed by as needed (PRN) retreatment. Results: Complete subretinal fluid resorption with adherence of the neurosensory retina was observed in all the 37 eyes; the mean number of intravitreal ranibizumab injections required was 4.56 ± 0.1. Over the 18-month follow up period, best-corrected visual acuity (BCVA) improved from 0.12 ± 0.03 to 0.42 ± 0.04 in 27 eyes (72.97%). OCTA patterns of CNV activity tended to fade, with the characteristic presence of isolated long filamentous vessels having a "dead tree" appearance. Conclusion: Application of OCTA, an information-rich modality, in pathological myopia, facilitates a personalized approach to determining the need for anti-VEGF therapy and selecting the mode of administration of anti-VEGF agents based on the CNV activity.